A Detail Description on Catalytic Conversion of Waste Palm Cooking Oil into Biodiesel and Its Derivatives: New Functionalized Ionic Liquid Process. Issue 27 (22nd September 2017) - Ullah, Zahoor; Bustam, Mohamad Azmi; Man, Zakaria; Khan, Amir Sada; Muhammad, Nawshad; Sarwono, Ariyanti; Farooq, Muhammad; Ullah, Riaz; Mengal, Ali Nawaz
Abstract: This work is focusing on the synthesis and application of new potential ionic liquids (ILs) for biodiesel production from waste palm cooking oil. For this propose total eleven ionic liquids were synthesized containing various types of cations and anions and characterized with nuclear magnetic resonance (NMR), fourier‐transform infrared (FTIR) and elemental analyser (CHNS). The Hammett acidity of the ionic liquids were determined using Ultraviolet (UV ) visible spectrometer and correlated with their catalytic properties. The process of biodiesel preparation has been optimized with respect of different factors (catalysts concentrations, methanol to oil ratio, temperature, agitation speed and time) affecting the transesterification reaction. The highest yield of 96.25% for 3‐methyl‐1‐(4‐sulfo‐butyl)‐3H‐imidazol‐1‐ium trifluoromethanesulfonate [BSMIM][CF3 SO3 ] was obtained under optimal conditions. The obtained product was characterized using gas chromatography (GC), NMR, FTIR, Thermogravimetric analysis (TGA) techniques. The physicochemical properties like kinematic viscosity, flash point, density etc were determined and compared with the standard of American Society of Testing Materials (ASTM) and European Standard (EN) methods. The by‐product of reaction i.e. glycerol was further esterified to minimize the waste of glycerol. The kinetic study shows that the transesterification reaction catalysed by prepared ILs follow the pseudo‐first order reaction. The kinetic energy ( Ea ) of the reaction was calculated around 19.89 kJ/mol. Abstract : Ionic liquids (ILs) as perspective catalysts for biodiesel production especially form high FFAs oils and convert their triglycerides into esters. It is highly recyclable and reusable catalysts. Now a days ionic liquids have a lot of applications and due to their unique properties, they are getting popularity in academics as well as in industries. This study also presents the protocol for ionic liquids to be used as catalysts for biodiesel production by transesterification process.